PREVALENSI DAN KARAKTERISTIK PERDARAHAN ANTEPARTUM DI RUANG RAWAT INAP OBSTETRI DAN GINEKOLOGI DI RSPAL DR. RAMELAN SURABAYA - I Ketut Edy Sudiarta (Oceana Biomedicina Journal, 2023)
Background: Bleeding in obstetrics is one of the main causes of maternal mortality. Based on the 2017 World Bank report, in 1 day there are 4 mothers in Indonesia who die due to childbirth. One of the main causes of maternal mortality is antepartum bleeding, as well as preeclampsia and infection. The incidence and characteristics of antepartum bleeding cases are not known with certainty. In this study, we wanted to know the characteristics and prevalence of antepartum bleeding at the Obstetrics and Gynecology Laboratory, RSPAL Surabaya. Methods: A descriptive retrospective study that used a cross-sectional approach to determine the prevalence and characteristics of antepartum bleeding in the Obstetrics-Gynecology Laboratory of the Naval Center Hospital, Dr. Ramelan Surabaya for the period 2019 to 2021. Results and Conclusions: The prevalence of antepartum bleeding in the Obstetrics and Gynecology laboratory during the period January 2019 – December 2021 was 29.9% (91 out of 304 deliveries), with the highest age group being 30-34 years as many as 31 people (34.1%), parity ( P2) mostly 34 patients (37.4%). Based on gestational age, 50 people (54.9%) gestational age <37 weeks, 51 cases (56%) placenta previa and 39 cases (42.8%) placenta accreta/percreta. Case management, 81 cases (89%) were terminated via sesarean section.